Gender impact on quality of life in colorectal cancer survivors - Grbič, Aleksandra (Radiology and oncology (Ljubljana), 2025)
The aim of the study was to evaluate gender-specific differences in the quality of life (QoL) and late effects among colorectal cancer patients during the first two years after treatment, to inform and improve long-term follow-up care and clinical management strategies. Patients and methods A total of 239 colorectal cancer patients were included, 56% males and 44% females, mostly in the age range 60–69 years. They were treated at the Institute of Oncology Ljubljana, during the time period from 1st September 2023 to 1st May 2024. In addition to demographic data, we included clinical data on disease and outcomes collected using the standardized quality of life questionnaires of European Organization for Research and Treatment of Cancer (EORTC) named EORTC QLQ-30 and EORTC QLQ-CR29 for colorectal cancer, respectively. Results Females were more likely to experience emotional problems (p = 0.002), higher levels of fatigue (p < 0.001), insomnia (p = 0.015), nausea and vomiting (p = 0.007), which may also be associated with poorer appetite in females. Males reported better body image than female (p = 0.047), lower levels of anxiety (p = 0.029), less frequently reported perceived weight loss or gain (p = 0.010). Male reported more stool frequency (p = 0.045), and also had more sever dysuria compared to female (p = 0.008). Conclusions The results provide the opportunity to improve the clinical management of long-term follow-up and care planning, taking into consideration the gender-specific needs of colorectal cancer survivors.
Keywords: colorectal cancer; kakovost življenja; late effects; pozne posledice; quality of life; rak debelega črevesa in danke